2017
DOI: 10.1002/jib.448
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion of brewers' spent grains and application in the production of functional food. Characteristics of spent grains and optimization of extrusion

Abstract: Brewers' spent grains (BSG) form 85% of the waste products from the brewing process. BSG contain a number of substances with functional benefits and can be used for the production of new food types. The present publication considers the main characteristics of BSG derived from six malt types: light barley malt, Pilsner malt, wheat malt, Munich malt type II, Vienna malt and Carafa malt type III. The spent grain starch content, the degree of starch gelatinization, the phenolic compound content and the antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…The antioxidant activity of MB (Table ) was 30.05% for the ABTS method, 12.86% for DPPH, and 7.22 mg GAE/g for FRAP, while TPC was 1.79 mg GAE/g. For the TPC, similar values were obtained by Ivanova et al (), in the range 1.30–1.60 mg GAE/g for MB from different malts, and for Carafa malt, the content was >2.00 mg GAE/g.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The antioxidant activity of MB (Table ) was 30.05% for the ABTS method, 12.86% for DPPH, and 7.22 mg GAE/g for FRAP, while TPC was 1.79 mg GAE/g. For the TPC, similar values were obtained by Ivanova et al (), in the range 1.30–1.60 mg GAE/g for MB from different malts, and for Carafa malt, the content was >2.00 mg GAE/g.…”
Section: Resultssupporting
confidence: 87%
“…Protein and fiber are also present because they are concentrated after the wort process, where the starch is removed (Kissel & Prentice, ). Vitamins, minerals, and amino acids (mainly valine, alanine, serine, glycine and glutamic, and aspartic acids) are also found in MB (Ivanova et al, ; Mussatto et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Brewer’s spent grain (BSG) corresponds to the main by-product of the brewery industry, and comprises insoluble fragments of malt remaining after barley malt mashing and filtration [21,22]. Dried BSG is a lignocellulosic material containing about 192 to 284 g/kg of hemicelluloses (xylose and arabinose), 168 to 254 g/kg of cellulose (glucose), 153 to 247 g/kg of proteins, 119 to 278 g/kg of lignin, and 12 to 46 g/kg of ashes [23].…”
Section: Introductionmentioning
confidence: 99%
“…(2013) indicated that the highest content of antioxidants in BSG determined by FRAP was 0.02 µmol mg −1 , while Ivanova et al . (2017) reported 0.006 and 0.005 µmol mg −1 according to FRAP and DPPH assays. Although ABTS assay did not indicate any significant difference among the samples ( P > 0.05), the antioxidant capacity determined with this method was also significantly higher than previous studies.…”
Section: Resultsmentioning
confidence: 99%